Modelling of progressive fibre/matrix debonding in short-fibre reinforced composites up to failure. (1st August 2015) - Notta-Cuvier, D.; Lauro, F.; Bennani, B.
Abstract: Mechanical behaviour of short-fibre reinforced composites (SFRC) can be affected by numerous damage phenomena. This paper focuses on the modelling of fibre/matrix debonding initiated at fibre tips, which is the dominant damage mechanism when a majority of short-fibres are subjected to local tensile loadings. A failure criterion for SFRC is proposed based on a critical amount of voids located in debonded areas. Very accurate mechanical states at break can be predicted for SFRC with complex fibre distribution of orientation, for different kinds of uniaxial and biaxial tensile loadings.